Effects of Propranolol, a β-noradrenergic Antagonist, on Memory Consolidation and Reconsolidation in Mice - Villain, Hélène; Benkahoul, Aïcha; Drougard, Anne; Lafragette, Marie; Muzotte, Elodie; Pech, Stéphane; Bui, Eric; Brunet, Alain; Birmes, Philippe; Roullet, Pascal (Frontiers in Behavioral Neuroscience, 2016)
Memory reconsolidation impairment using the β-noradrenergic receptor blocker propranolol is a promising novel treatment avenue for patients suffering from pathogenic memories, such as post-traumatic stress disorder (PTSD). However, in order to better inform targeted treatment development, the effects of this compound on memory need to be better characterized via translational research. We examined the effects of systemic propranolol administration in mice undergoing a wide range of behavioral tests to determine more specifically which aspects of the memory consolidation and reconsolidation are impaired by propranolol. We found that propranolol (10mg/kg) affected memory consolidation in non-aversive tasks (object recognition and object location) but not in moderately (Morris water maze) to highly (passive avoidance, conditioned taste aversion) aversive tasks. Further, propranolol impaired memory reconsolidation in the most and in the least aversive tasks, but not in the moderately aversive task, suggesting its amnesic effect was not related to task aversion. Moreover, in aquatic object recognition and location tasks in which animals were forced to behave (contrary to the classic versions of the tasks); propranolol did not impair memory reconsolidation. Taken together our results suggest that the memory impairment observed after propranolol administration may result from a modification of the emotional valence of the memory rather than a disruption of the contextual component of the memory trace. This is relevant to the use of propranolol to block memory reconsolidation in individuals with PTSD, as such a treatment would not erase the traumatic memory but only reduce the emotional valence associated with this event.